Labs in the Real World. Advancing Transdisciplinary Research and Sustainability Transformation: Mapping the Field and Emerging Lines of Inquiry. - Schäpke, Niko; Bergmann, Matthias; Stelzer, Franziska; Lang, Daniel J. (Oekom, 2018)
There is a strong trend towards research in society-based laboratories, especially in relation to sustainability. Semantic analysis reveals related discourses and emerging lines of inquiry, namely transformative potential, transdisciplinarity and learning. Real-world laboratories are a dynamic example of this research. Contributions of how to deepen and broaden their analysis are presented.
Keywords: Nachhaltige Entwicklung; Forschungsmethode; Wissenstransfer; Reallabor; Begriffsbestimmung; Literaturrecherche; Transdisziplinarität